Introduction to the special issue: Current challenges and future prospects of entrepreneurship in Nordic and Baltic Europe. Issue 2 (4th April 2016) - Shneor, Rotem; Jenssen, Jan Inge; Vissak, Tiia
Abstract : Purpose: – The purpose of this paper is to set the papers included in the special issue into their unique contextual stage of entrepreneurial eco-systems in Nordic and Baltic countries. Design/methodology/approach: – The editorial first presents the current status of entrepreneurship in the Nordic and Baltic regions. It then provides an overview of the papers included in this special issue, while highlighting their contributions. Finally, it concludes with suggestions for further research, while pointing out promising areas for future investigations. Findings: – The papers included in this special issue help advance the understanding of important aspects of entrepreneurship in general, and within the context of Nordic and Baltic countries in particular. The first two papers focus on antecedents of entrepreneurial behaviour, namely – education and passion, while the last two papers address entrepreneurial behaviour and its outcome in terms of both growth aspiration and actual growth. Finally, the editorial identifies three important themes for future research, namely – the roles of Web 2.0 and online communities, crowdfunding and alternative finance, as well as current immigration trends on entrepreneurship development and dynamics in Nordic and Baltic Europe. Originality/value: – This editorial and special issue are in tune with current calls for better understanding of entrepreneurship-related phenomena within their social context, and some of the linkages between social settings and manifestations of entrepreneurship. And while most papers concentrate on themes that may be associated with mainstream entrepreneurship research, each introduces new angles and/or conceptual combinations surrounding such themes and variables, which are unique and inspirational.